Corporate Governance and Non Performing Financing on Sharia Bank Profitability - Retno Puji Astuti; Mariyam Chairunisa (Universitas Mercu Buana, 2021)
This study aims to examine impact of Corporate Governance and Non Performing Financing on sharia bank profitability. The unit analysis of this research is Sharia Banks in Indonesia which have been registered in the Financial Services Authority (OJK) period 2013 to 2017. This research was done on 13 Islamic commercial banks by using quantitative-descriptive approach. The results of this research showed that Corporate Governance that represented by institutional ownership has negative effect and insignificantly on profitability. Board meeting has positive affect and significant on profitability. Board size and audit committee size have positive effect and significant on profitability. However, Non Performing Financing has a negative effect and significant on profitability.